UPAYA PENINGKATKAN MOTIVASI DAN PRESTASI BELAJAR IPS MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT - Maisaroh, Siti (Dinamika Pendidikan, 2011)
The objective of the study was to know the improvement of studentsâ motivation and achievement with Cooperative learning at Team Games Tournament (TGT) Model. The subject of study was IV grade students in SDN Sungapan, Bantul Games Tournament (TGT) Model in the teaching learning process. The steps of procedure in conducting the research were planning, implementation, observation via questionnaire, test, interview and field notes. Then, the data were analyzed quantitatively and qualitatively. Descriptive analysis was used to describe the result of observation. The result of the research showed that there was improvement of studentsâ motivation and achievement on IV grade students of SDN Sungapan Bantul with Team Games Tournament (TGT) Model. At the beginning, the average of studentsâ motivation was 67.17% (average category), then it increased up to 73,35% (high category) on the 1st cycle, and rose to 80.75% (high category) on the 3rd cycle. Where as, studentsâ achievement at beginning was only 67.64 with classical completeness was 39.28%, and then increased up to 79.6 with classical completeness was 85.28% on the 2nd cycle. Based on the result above, it can be concluded that the implementation of Cooperative learning at Team Games Tournament (TGT) Model can improve studentâs motivation and achievement on IV grade students in SDN Sungapan Bantul in learning Social Science.